The Construction of Village Kiai Identity in Non-Formal Education - M. Ainul Yaqin (Journal of Research in Educational Management, 2023)
Obedience and submission to the individual are related to the doctrine of the mind of every other individual. The role of interaction between individuals is very meaningful in the social order. Individual compliance will be examined in the construction of the self-identity of individual community leaders. This study aims to reveal the form of identity construction of the village kiai in Pajurangan and the characteristics of the transformational leadership of the village kiai as managers of non-formal education in the northern coastal community of Probolinggo. This research uses a qualitative approach with the type of case study research. With the aim of explaining the actual situation in the community in full, in depth, in detail, as it is for the development of the community concerned. The presence of the researcher in this case is absolutely used because the researcher is the key instrument (main actor). The data that has been collected is in accordance with the existing cases (case studies) which include domain analysis, taxonomic analysis, compenesial analysis, and analysis of cultural themes. The results of this study indicate that: 1) The identity construction of the village kiai in the Pajurangan community goes through three dialectical processes. The first is the externalization process, the second is the objectivation process, and the third is the internalization process. 2) The transformational leadership of the village kiai in Pajurangan has four leadership characteristics, namely: charisma, individual considerations, intellectual stimulation, and inspirational motivation.